FORENSIC EXAMINATION OF THE CAUSES OF SUDDEN DEATH (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
The analysis of the causes of sudden death of the general population and individuals aged 18 to 40 years was based on a retrospective study of forensic data conducted over three years. It has been established that one of the main causes of the sudden death of the young is cardiovascular pathology, which is associated with the anterior inflammation of the connective tissues. The main mechanism of sudden cardiac death in this age group is the arrhythmogenic mechanism. The development of terminal symptom complexes is facilitated by triggering factors, such as physical tension, psycho-emotional stress, and alcohol use.